2016
DOI: 10.21833/ijaas.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating pre-service teacher academic achievement through problembased learning (PBL)

Abstract: This study is focused on Problem-Based Learning (PBL) methodology and academic achievement due to the fact that academic achievement is a core learning process which also involves a problem solving task. A quasiexperimental design was employed in this study, where 45 pre-service teachers undertaking a B. Ed (Economics) were randomly assigned to the experimental (n=23) and control groups (n=22). The PBL method was utilised in the experimental group while the traditional learning method was utilised in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As an educational method, PBL has been gaining ground and many studies point out several advantages: student satisfaction [28], ability to integrate new information into previous knowledge [29], a greater ability to transfer concepts to new problems [30], better results [31], development of various general skills [32], increasing student attitudes and interest in a STEM career [33], providing more opportunities for students' collaboration, and, thus, promoting higher-order thinking skills [5] and enhancing student achievement [34], among others. In broader studies, literature reviews and meta-analyses reported positive reactions to the methodology [35], gains in attitudes [36], and retention of knowledge for longer periods of time compared to the traditional methodology [37], increasing articulation compared to other active learning strategies [20], but not always better academic results [38].…”
Section: Introductionmentioning
confidence: 99%
“…As an educational method, PBL has been gaining ground and many studies point out several advantages: student satisfaction [28], ability to integrate new information into previous knowledge [29], a greater ability to transfer concepts to new problems [30], better results [31], development of various general skills [32], increasing student attitudes and interest in a STEM career [33], providing more opportunities for students' collaboration, and, thus, promoting higher-order thinking skills [5] and enhancing student achievement [34], among others. In broader studies, literature reviews and meta-analyses reported positive reactions to the methodology [35], gains in attitudes [36], and retention of knowledge for longer periods of time compared to the traditional methodology [37], increasing articulation compared to other active learning strategies [20], but not always better academic results [38].…”
Section: Introductionmentioning
confidence: 99%